PEMANFAATAN AUGMENTED REALITY UNTUK PEMILIHAN PAKAIAN ADAT NTT - William Mosa Muku; Marselina Uda (Lembaga Pengembangan Kinerja Dosen, 2026)
This research aims to develop an application based on Augmented Reality technology to facilitate the virtual selection of traditional clothing from East Nusa Tenggara . AR technology allows users to view and try on traditional clothing through real-time 2D models. The research focuses on designing and implementing an Androidbased system that integrates modern technology with the preservation of traditional culture. The methodology involves Visual studio code-based development and data collection from academic literature and interviews with cultural experts. This application is expected to enhance public awareness and appreciation of East Nusa Tenggara cultural heritage. The research contributes to the utilization of technology for cultural preservation through an innovative approach.